Dynamics of Physical Preparedness of LASE Students in Revelation to the Number of Practical Methodological Classes - Lesčinskis, Māris; Čupriks, Leonīds; Ciematnieks, Uģis; Saulīte, Sergejs; Glazkovs, Genādijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the tasks in study course “Athletic preparation” is to develop strength abilities, and, after study course, to determine development level of strength abilities. Planning of study course “Athletic preparation” in the period from 2005/2006 to 2008/2009 year of study, the practical methodological classes was different. In the period from 2005/2006 to 2006/2007 year of study the practical methodological classes was planned three times per week. In the period from 2007/2008 to 2008/2009 year of study the practical methodological classes was planned one time per week. On the basis of the study schedule changes there was the assumption that, planning study course “Athletic preparation” all year once a week, it is not possible to achieve as good physical development as during three classes per week planning during one semester. Evaluation of physical preparedness dynamic of LASE first course students in the study course “Athletic preparation” with a variety of practical methodological classes will allow us to evaluate the effectiveness of study courses releated to physical preparedness. Research data obtained will make it possible in the future to better plan the different course volume and incidence of classes, associated with increasement of physical preparedness.